Agro-morphological characterization of Indian garlic (Allium sativum L.) germplasm under mid hill of Northwest Himalaya - Rahul Dev; N.K. Hedau; S. Santhiya; R.S. Pal; Amit Paschapur; Lakshmi Kant (Advances in Horticultural Science)
This study evaluated the genetic diversity of Indian long-day garlic genotypes based on agro-morphological and biochemical traits. A significant variation was observed across 23 traits, indicating high genetic diversity. Key traits such as bulb weight and 20-clove weight, leaf thickness, and clove showed substantial variability and antioxidant properties highlighted the potential for developing high-quality garlic varieties. Hierarchical cluster analysis grouped 94 genotypes into four clusters based on key traits, emphasizing their utility for breeding programs. Genotypes VGS-55 and VGS-43 excelled in growth traits, while VGS-51 and VGS-49 demonstrated superior biochemical content. Principal component analysis (PCA) revealed that the first two components accounted for 40.73% of the total variability, with yield-promoting traits dominating PC1 and biochemical traits influencing PC3. Trait association studies indicated strong positive correlations between bulb yield and traits like bulb weight (r=0.97 ***) and equatorial diameter (r=0.73 ***), whereas no significant association was observed between bulb yield and biochemical traits. These findings underscore the immense genetic potential within Indian garlic germplasm for breeding programs targeting higher yields and improved biochemical traits, catering to the increasing demand for both bulbs and fresh garlic leaves in India.